Pengalaman Ujaran Kebencian di Media Sosial dan Kondisi Emosional Siswa Kelas X SMA - Tarbita Dwi Fajarienna; Makin Syuhadak (Indonesian Journal of Educational Counseling, 2026)
This study aimed to identify the forms of hate speech experienced by tenth-grade students at SMA Negeri 1 Minggir, describe students’ emotional conditions associated with hate speech on social media, describe how students respond to such hate speech, and describe the role of Guidance and Counseling services in helping students cope with the impact of hate speech on social media.This study employed a qualitative approach with a descriptive qualitative design. The subjects of the study were 6 tenth-grade students, selected purposively based on inclusion criteria. The data were collected through structured interviews and non-participant observation. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, which consists of data reduction, data display, and conclusion drawing. The findings revealed that: (1) the forms of hate speech experienced by students included body shaming (28%), social comparison (22%), negative comments and harsh words (20%), negative talk in group chats (18%), and accusations or false allegations (12%); (2) the emotional conditions associated with these experiences included sadness (18%), hurt (14%), anxiety (12%), anger (10%), discomfort (10%), shame (8%), restlessness (8%), decreased self-confidence (8%), annoyance (6%), and fear (6%), ranging from momentary reactions to more persistent conditions; (3) students responded by remaining silent (25%), seeking support from trusted people (25%), ignoring comments (20%), reducing social media use (20%), and calming themselves (10%); and (4) Guidance and Counseling services at school had not fully addressed the issue of hate speech, indicating the need for more targeted, proactive, and responsive counseling programs.